Navigating Modernity: Ethical Practices and Islamic Economic Values Among Traditional Second-Hand Goods Traders - Mawardi, Mawardi,; Bustami, Zulfahmi; Norhiza, Fitra Lestari; Darussamin, Zikri; Syaputra, Widi; Maulidizen, Ahmad (Journal of Ecohumanism, 2025)
This study investigates the integration of Islamic values and modernization in the practices of second-hand goods traders in traditional markets within Riau Province. Using a qualitative approach, the research employed semi-structured interviews and a hierarchical analysis process (AHP) questionnaire to assess the weight of various indicators related to Islamic economic ethics and market modernization. The sample included academics, market officials, market association leaders, and business owners. Key findings reveal that Islamic values, particularly the avoidance of usury, are highly emphasized among traders, with an achieved weight of 65%. Indicators such as avoiding usury and ensuring product quality were rated significantly, with weights of 40% and 36%, respectively. The study highlights that while Islamic values are well integrated, social and cultural factors remain a challenge. The lowest weight was observed in the social and cultural dimensions, indicating a need for increased community engagement and modern market practices to boost consumer trust and sales quality. The implications suggest that policymakers should focus on promoting ethical trading and market modernization, while educational programs can enhance traders’ understanding of Islamic economic principles. Future research could expand to other regions and explore the impact of technological advancements on market practices and Islamic values. This study provides a foundational understanding of how traditional markets can align with modern values while adhering to Islamic principles.